Controlled synthesis of core-shell carbide-derived carbons through in situ generated chlorine - Ariyanto, Teguh; Zhang, Guirong; Riyahi, Farshad; Gläsel, Jan; Etzold, Bastian (Carbon, 2017)
Core-shell porous carbon represents an innovative concept for optimizing performances of carbon materials in a wide range application. Here, a novel route to produce carbons with spatially varying pore and microstructure is presented. Following the carbide-derived carbon method, a homogeneous and adjustable shell generation is achieved through mixing a limited amount of solid chlorine precursors with titanium carbide raw material. Chlorine is released in situ when reaching approx. 600 °C and consumed subsequently directly, resulting in the aspired materials. Various characterization methods proved that the amount of solid chlorine precursor directly adjusts the share of the shell for the core-shell material, while a range of 5–80% was studied. The amorphous, microporous shell can be converted to a mesoporous and graphitic shell (crystal sizes 20 nm), through a subsequent vacuum annealing, allowing to control the properties of the carbon shell. The carbon core results after a subsequent second chlorination step, where directly gaseous chlorine is used. The materials were characterized in detail after every step of this novel route. Adjusting the share between mesoporous/graphitic shell and microporous/amorphous core for these new materials is of interest in applications where competing processes like mass transfer and surface interaction need to be optimized.
CRIS-Team Scopus Importer:2023-08-15